'I went and prayed to have my name put down in the missionaries' book': gift exchange and Bible transactions in Britain and Antigua, 1834–1884. Issue 10 (3rd October 2022) - Sixsmith, Lucy
ABSTRACT: In the archives of the Bible Society at Cambridge University Library, there are two New Testaments presented to black Antiguan Christians in the 1830s as part of a commemoration project following formal emancipation of enslaved people on 1 August 1834. They were marked as a gift by the Society, with a cover stamp and presentation label. After several decades of handling, they were given back to Bible Society representatives. This essay weighs the meaning of each act of giving, reading the evidence of the material text alongside the Bible Society's documentation, scholarship in the history of emancipation, and writing on gift theory, primarily by Pierre Bourdieu. The Society's project was an act of distraction or self-deception: abolitionists and missionaries were glad to think of themselves as generous benefactors. However, their idea of the gift, imposed from above like an impression on a leather cover, could not dictate the volumes' whole history. Marks in each volume show how their readers put them to use in their own way. The return gift can be read as an expression of agency, inserting the religious and reading experiences of a community into the Bible Society's archives.